Analysis of the Financial Capabilities and Performance of Local Goverments in Muaro Jambi District - Putri, Villya Marsheela; Sam, Iskandar; Erwati, Misna (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the Financial Capability and Financial Performance of Regional Governments in Muaro Jambi Regency using the Financial Capability Index, Permendagri Number 62 of 2017, Independence Ratio, Fiscal Decentralization Degree Ratio, Effectiveness Ratio, Activity Ratio, and Regional Expenditure Compatibility Ratio. The results of this study indicate that the value of the Financial Capability Index of the Muaro Jambi Regency Government is in the medium category. According to Permendagri Number 62 of 2017, it is included in the low criteria. The Independence Ratio is in the very low category. The Fiscal Decentralization Degree Ratio is in the low category. The Effectiveness Ratio is in the highly effective category. Then the Activity Ratio shows that the Government allocates more funds for Apparatus Expenditure than Public Expenditure. The Regional Expenditure Compatibility Ratio shows that the government allocates more funds to Direct Expenditure.